Controlling the Urban Physical Development in Karawang and Purwakarta Regencies using Quantitative Zoning Approach - Alfin Murtadho; Andrea Emma Pravitasari; Khursatul Munibah; Izuru Saizen; Ernan Rustiadi (Faculty of Geography, Universitas Gadjah Mada, 2022)
Jakarta and Bandung metropolitan areas in Indonesia are experiencing urban expansion, which makes these two metropolitan areas increasingly connected by corridors to become one mega-urban. Karawang and Purwakarta Regencies are part of the Jakarta-Bandung corridor area which then triggers the urban physical development. This study aims to 1) Determine the level of service facilities in Karawang and Purwakarta Regencies; 2) Identify the changes in built-up and paddy fields Land Use/Land Cover (LULC) of Karawang and Purwakarta Regency based on existing and future conditions, and 3) Propose recommendations to control the urban physical development in Karawang and Purwakarta Regency. Analysis of level service facilities was carried out by using the scalogram method. Changes of built-up and paddy fields LULC in the existing and future conditions (projected using the CA-Markov method) are based on LULC of 2005, 2010 and 2018. Recommendations are given based on the grouping of villages with the same characteristics using the quantitative zoning method. Results showed the village development index in 2018 as the level of service facilities indicators, has a high or more developed value in the area around the connecting accessibility route between Jabodetabek and Greater Bandung metropolitan area. Changes in built-up and paddy fields LULC also the same trend as the village development index that is characterized by a fairly large increase in the area of built-up LULC in Karawang and Purwakarta Regencies. Recommendations are given to address specific problems that exist in each village group formed based on the spatial clustering method result.